(untitled) (Quinto Sol, 2021)
This paper analyzes the trajectory of two indigenous communities from Neuquen through one century, focusing on the paths followed to access and remain in their territories, as well as the highs and lows in relation to their persistence as mapuche communities. The main goal was to explain how they achieved their current state of community reconstitution, and their relationship with politics at a provincial level, specifically in the context of the development of a new political line within the Confederación Mapuche de Neuquén at the beginning of this century. The article studied the factors that, from the genocide to the native peoples on, conditioned their possibilities of staying cohesive in a context of struggle with dominant territorialities: public policies on access to land, designed by the National State first, and then by the province, the actions of different agents in office, the mapuche political praxis and the bond they established with their supracommunal organizations. The heterogeneity of situations in the space of Neuquen led to define two cases to develop the analysis: Paicil Antriao, in the southern Andes area, and Campo Maripe, in the central eastern plateau zone.